Enhancing multifunctionality in European boreal forests: The potential role of Triad landscape functional zoning - Blattert, Clements; Eyvindson, Kyle; Mönkkönen, Mikko; Raatikainen, Kaisa J; Triviño, María; Duflot, Rémi (Elsevier, 2023)
Land-use policies aim at enhancing the sustainable use of natural resources. The Triad approach has been suggested to balance the social, ecological, and economic demands of forested landscapes. The core idea is to enhance multifunctionality at the landscape level by allocating landscape zones with specific management priorities, i.e., production (intensive management), multiple use (extensive management), and conservation (forest reserves). We tested the efficiency of the Triad approach and identified the respective proportion of above-mentioned zones needed to enhance multifunctionality in Finnish forest landscapes. Through a simulation and optimization framework, we explored a range of scenarios of the three zones and evaluated how changing their relative proportion (each ranging from 0 to 100%) impacted landscape multifunctionality, measured by various biodiversity and ecosystem service indicators. The results show that maximizing multifunctionality required around 20% forest area managed intensively, 50% extensively, and 30% allocated to forest reserves. In our case studies, such landscape zoning represented a good compromise between the studied multifunctionality components and maintained 61% of the maximum achievable net present value (i.e., total timber economic value). Allocating specific proportion of the landscape to a management zone had distinctive effects on the optimized economic or multifunctionality values. Net present value was only moderately impacted by shifting from intensive to extensive management, while multifunctionality benefited from less intensive and more diverse management regimes. This is the first study to apply Triad in a European boreal forest landscape, highlighting the usefulness of this approach. Our results show the potential of the Triad approach in promoting forest multifunctionality, as well as a strong trade-off between net present value and multifunctionality. We conclude that simply applying the Triad approach does not implicitly contribute to an overall increase in forest multifunctionality, as careful forest management planning still requires clear landscape objectives.
Keywords: Ecosystem services; Forest management; Forest planning; Land sparing; Land sharing; Landscape planning; Multi-objective optimization